2011
DOI: 10.1111/j.1540-5907.2011.00548.x
|View full text |Cite
|
Sign up to set email alerts
|

How Trust Matters: The Changing Political Relevance of Political Trust

Abstract: Americans most often think about government in terms of its ability to grapple with issues of redistribution and race. However, the September 11 terrorist attacks led to a massive increase in media attention to foreign affairs, which caused people to think about the government in terms of defense and foreign policy. We demonstrate that such changes in issue salience alter the policy preferences that political trust shapes. Specifically, we show that trust did not affect attitudes about the race‐targeted progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
127
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(140 citation statements)
references
References 40 publications
8
127
1
4
Order By: Relevance
“…Prior research has generally considered political trust to be about people's satisfaction with their governments' overall performance (e.g., Hetherington 2005;Hetherington and Husser 2012;Hetherington and Rudolph 2015;Rudolph 2009;Rudolph and Evans 2005). In contrast, the present study isolates cynicism-perceptions of a lack of honesty and integrity on the part of public officials-and finds that this sentiment by itself exercises considerable influence on people's attitudes.…”
contrasting
confidence: 40%
“…Prior research has generally considered political trust to be about people's satisfaction with their governments' overall performance (e.g., Hetherington 2005;Hetherington and Husser 2012;Hetherington and Rudolph 2015;Rudolph 2009;Rudolph and Evans 2005). In contrast, the present study isolates cynicism-perceptions of a lack of honesty and integrity on the part of public officials-and finds that this sentiment by itself exercises considerable influence on people's attitudes.…”
contrasting
confidence: 40%
“…Legitimacy is a resource that frees governments to undertake programs that are unpopular in the short run (Dalton, 2004;Hetherington, 1998;Hetherington & Husser, 2011;Levi & Stoker, 2000). Enduring support for a regime's institutions and values thus contributes to its effectiveness and stability, as well as to a polity's ability to fend off non-democratic challenges (Easton, 1965;Lipset, 1959).…”
Section: Multicultural Policy and Political Supportmentioning
confidence: 99%
“…Empirical research undertaken has also confirmed that the absence of voter trust has a profound impact on voting behaviour (Hetherington, 2005;Hetherington & Husser, 2012;Pauwels, 2010). (Pauwels, 2010).…”
Section: Voter Trustmentioning
confidence: 99%
“…If the government is delivering on its promises, trust is enhanced and if it doesn't, colossal trust deficit prevails. Just as much as trust plays a pivotal role in the business arena, it also plays a huge role in the political arena and is a cornerstone of citizen support, it enhances citizen co-operation and compliance with government demands such as taxpaying and fortifies political participation through elections (Hetherington & Husser, 2012). The concept of customer loyalty has occupied centre stage in marketing literature as it is regarded as one of the company's most enduring assets.…”
Section: Voter Trust and Voter Loyaltymentioning
confidence: 99%